2020
DOI: 10.1002/aenm.201903354
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Losses and Assessing the Photovoltage Limits in Metal–Insulator–Semiconductor Water Splitting Systems

Abstract: Metal–insulator–semiconductor (MIS) photo‐electrocatalysts offer a pathway to stable and efficient solar water splitting. Initially motivated as a strategy to protect the underlying semiconductor photoabsorber from harsh operating conditions, the thickness of the insulator layer in MIS systems has recently been shown to be a critical design parameter which can be tuned to optimize the photovoltage. This study analyzes the underlying mechanism by which the thickness of the insulator layer impacts the performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(83 citation statements)
references
References 64 publications
1
69
0
Order By: Relevance
“…This also can affect the recombination rates and impact the photovoltage. [4,[31][32][33][34] iv) The geometry of the interfacial contact area will also modulate the transfer of charge carriers across the interface, i.e., the rate of the collection of charge carriers by the EC is affected by the interfacial contact EC/SC area. [35] To test whether the barrier height is different for the oxidized Si interface in contact with Ni compared to the non-oxidized Si/Ni interface (mechanisms i and ii above), we performed the Mott-Schottky analysis (see Supporting Information for details).…”
Section: Physical Electrochemical and Atomistic Characterization Of P...mentioning
confidence: 99%
See 1 more Smart Citation
“…This also can affect the recombination rates and impact the photovoltage. [4,[31][32][33][34] iv) The geometry of the interfacial contact area will also modulate the transfer of charge carriers across the interface, i.e., the rate of the collection of charge carriers by the EC is affected by the interfacial contact EC/SC area. [35] To test whether the barrier height is different for the oxidized Si interface in contact with Ni compared to the non-oxidized Si/Ni interface (mechanisms i and ii above), we performed the Mott-Schottky analysis (see Supporting Information for details).…”
Section: Physical Electrochemical and Atomistic Characterization Of P...mentioning
confidence: 99%
“…To describe and quantify how these atomistic changes to the EC/SC interface impact the system performance, we developed an analytical model that can capture the behavior of the systems. The model is based on the illuminated diode equation, in which the relationship between the photovoltage (V ph ) and the net current (J net ) through an EC/SC interface is given by the following expression: [31] ln…”
Section: Modeling Of the Photoelectrocatalysts Behaviormentioning
confidence: 99%
“…Interestingly, the surface dipole induced by the chemical interaction; in other words, the replacement of hydroxyl groups with electron-withdrawing phosphonate groups strongly affects the surface [95][96][97]. And the phenyl moieties with various substituents change the higher electron-withdrawing abilities also increase the surface generated dipole [98,99] to change the barrier height at the interface (Figure 4b).…”
Section: Modulation Of Solid-solid Interface For Charge Transfer and mentioning
confidence: 99%
“…When the barrier height is small, thermionic emission charge transfer is dominant, while intraband tunneling occurs when the barrier height is large. Therefore, the characteristic charge transfer distance has a reverse-volcano relationship with the surface dipole and the barrier height [99]. Insertion of organic molecules at the solid-solid interface changes the charge transfer mechanism to Z-scheme charge transfer by band bending modulation at the interface.…”
Section: Modulation Of Solid-solid Interface For Charge Transfer and mentioning
confidence: 99%
“…Studies in the last decade have shown that chemical dynamics along the excited‐state PESs are accessible in plasmonic and hybrid plasmonic catalytic systems through localized surface plasmon resonance (LSPR)‐mediated electronic excitations. [ 2–20,22–34 ] The hybrid plasmonic photocatalytic approach is attractive for the conversion of solar energy into chemical energy, the development of coke‐resistant and selective catalytic processes, and the distributed synthesis of valuable chemicals with little to no requirement of external heating. [ 2–20,35,36 ] For example, Cu–Fe hybrid plasmonic nanocatalysts under visible‐light excitation exhibit high activity for ammonia (NH 3 ) synthesis at lower temperatures (30–42 °C) and atmospheric pressure, as compared to the Haber–Bosch process.…”
Section: Introductionmentioning
confidence: 99%